Streetscape planning guidelines for walkable campus - Amanina binti Nashar (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Walkability is an indicator for a walkable area and it is one of the fundamental principles to achieve sustainable environment. Streets that boost positive attachment between pedestrians and their surrounding would invite and attract more pedestrian utilization to it. This study focuses on street walkability on university campus. Recently, numerous Malaysian campuses are striving toward sustainability by promoting walking and cycling as a culture among students. This study believes that proper streetscape design is essential to enhance street walkability in campus. A walkable street comprises comfort, connectivity, safety and accessibility attributes to enhance the affinity of a street. The lack of concern for streetscape design, results in unfriendly street which seem to be the issue which requires fullest attention by campus planners. This study aims to overcome this shortcoming by suggesting possible streetscape guidelines to optimize streetscape design on campus for walkability enhancement. The objectives are to identify streetscape elements and walkability factors on Malaysian campus, to identify factors influencing pedestrian preferences of streetscape elements on campus, to assess the sidewalk design and determine the Pedestrian Level of Service(PLOS) and to suggest streetscape elements and composition for a walkable campus. Selecting the International Islamic University Malaysia (IIUM) Gombak as the site study, this research adopted a mixed method involving qualitative and quantitative approaches. The quantitative approach was conducted through pedestrian counting and questionnaire survey forms which were distributed among 425 IIUM students who lived on campus. Qualitative techniques involving the site inventory and observation, which aimed at assessing campus streetscape elements, were completed using the site inventory checklist. Frequencies, Relative Important Index (RII), Pedestrian Level of Service (PLOS), and Exploratory Factor Analysis (EFA) were used to analyzed the data. The findings indicate that comfort is the most significant factor contributing to street walkability, followed by safety, accessibility and connectivity. Pedestrian activities, physical safety, permeability and directness, pedestrian conflicts, ease of movement, traffic safety, vision at night, access to facilities, sidewalk connectivity and time/distance factors were 10 underlying sub-factors identified under these four main factors, which were highly influenced by streetscape elements that formed the streets area. All of these findings were later used to produce suitable streetscape guidelines for a walkable campus.